Depth coding and perceived quality for 3D video - Calemme, Marco; Cagnazzo, Marco; Pesquet-Popescu, Beatrice (2015 Seventh International Workshop on Quality of Multimedia Experience (Qomex), 2015)
Multi-view video plus depth is emerging as the most flexible format for 3D video representation, as witnessed by the current standardization efforts by ISO and ITU. The depth information allows synthesizing virtual view points, and for its compression various techniques have been proposed. We make a preliminary investigation of the effects on the synthesized views of two different approaches: object-based and block-based, from a perceptual point of view.